An axisymmetric Lattice Boltzmann Method Simulation of Forced Convection Heat Transfer for Water/Aluminum Oxide Nanofluid through a Tube under Constant Heat Flux on Wall - Reza Bahoosh; Reza Khalili; Amin Reza NoghrehAbadi; Mohamad Jokari (Journal of Heat and Mass Transfer Research, 2021)
Effects of different volumetric fractions and Reynolds number on forced convection heat transfer through water/aluminum oxide nanofluid in a horizontal tube are investigated. The flow regime is laminar and the method of simulation is the axisymmetric lattice Boltzmann method (ALBM). The profiles of velocity and temperature were uniform at the input section, on the tube walls the uniform heat flux was considered; moreover, hydrodynamic, and thermal development conditions at the output section were applied. It was observed that an increase in the volumetric concentration of the nanoparticles added to the forced convection heat transfer coefficient and Nusselt number of the nanofluid, as compared to the base fluid. For a volumetric fraction of 5% and Reynolds number of 100 at the input section of the tube (0.1≤X/D≤7) the forced convection heat transfer coefficient increased by 24.165%, while an average increase of 21.361% was observed along the entire length of the tube (0≤x/D≤30). A comparison between the improvements in heat transfer at the two input temperatures, it was found that the forced convection heat transfer coefficient and Nusselt number will increase further at the lower input temperature; Moreover, with increasing the Reynolds number, the percent improvements in forced convention heat transfer coefficient and Nusselt number increased.